Detecção de mudanças em florestas e savanas utilizando análise estatística baseada em objetos geográficos - Leite, Lucilia Rezende (2015)
The aim of this study was to evaluate the change detection on the ground cover in areas of Forest and Brazilian Savanna, using images from Landsat 5 / TM and two methodologies based on iterative statistics object. The sensitivity of the methods in relation to the heterogeneity of the input data was evaluated using the reflectance data and vegetation indexes, and the use of different levels of confidence. The periods analyzed comprised the years 2000 to 2006 and 2006 to 2010. After the segmentation of the images were extracted the quantities descriptive average statistics and standard deviation of each object. The determination of change of objects was carried out iteratively based on Mahalanobis Distance and the chi-squared distribution. The results were validated using a previous visual detection and analyzed according to the ROC curve. Significant gains have been made in the shade of use and the bands 3 and 4 for both areas tested with 94.67% and 95.02% of correctly detected objects as change respectively in the areas of Forest and Savanna. The use of NDVI and different images proved unsatisfactory for the detection of changes in the areas tested.